2021
DOI: 10.1016/j.compbiomed.2021.104360
|View full text |Cite
|
Sign up to set email alerts
|

Towards similarity-based differential diagnostics for common diseases

Abstract: Ontology-based phenotype profiles have been utilised for the purpose of differential diagnosis of rare genetic diseases, and for decision support in specific disease domains. Particularly, semantic similarity facilitates diagnostic hypothesis generation through comparison with disease phenotype profiles. However, the approach has not been applied for differential diagnosis of common diseases, or generalised clinical diagnostics from uncurated text-derived phenotypes. In this work, we describe the development o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…We also tested the setting that was used in our previous work, that is the combination of Resnik pairwise, BMA, and Resnik IC [23]. In this experiment, this yielded an AUC of 0.73, and an MRR-0 of 0.23, lower than the previously reported results of 0.77 and 0.42, respectively.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…We also tested the setting that was used in our previous work, that is the combination of Resnik pairwise, BMA, and Resnik IC [23]. In this experiment, this yielded an AUC of 0.73, and an MRR-0 of 0.23, lower than the previously reported results of 0.77 and 0.42, respectively.…”
Section: Discussionmentioning
confidence: 89%
“…One such area that the experimental platform could be turned towards, is the prediction of patient diagnosis through comparison with disease profiles, rather than with other patients. In our previous work, we identified that prediction of patient diagnosis from text-derived phenotypes was best when using SS to compare patients to disease profiles mined from literature, and extended with in-context training from patient profiles [23]. We plan to follow this study up with another, comparing patients with different sizes and derivations of disease profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to clustering, what remains to be done, is to determine a method that enables the re-integration of these scores, clusters, and groupings, into a single representation that minimises loss of information. Such an approach could lead to powerful insights into multi-and co-morbidity, as well as to improve semantic similarity based classification using text-derived phenotypes, such as that described by our previous work [11]. One method of approaching this specific to clustering problems could be the consideration of Multi-View Clustering, which could consider each measure of facet-wise similarity as a different view of the same patient admission [54], which could then be further analysed to determine an optimal set of clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Ontology-based analysis has been leveraged across many tasks including prediction of protein interaction and rare disease variants [1]. In the clinical space, similar analysis methods have been applied across a wide range of applications including diagnosis of rare and common diseases [2,3], as well as the identification of subtypes of diseases, such as autism [4]. In addition, the synthesis of ontology-based methods and machine learning is increasingly common [5].…”
Section: Introductionmentioning
confidence: 99%